2010
DOI: 10.2214/ajr.09.4032
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Dose Estimates in Body CT

Abstract: Embryo doses can be estimated using relative uterus doses, normalized plateau uterus doses, and CTDI(vol) data with correction factors for patient size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The latter approach, first proposed by Huda et al [21], provides an accurate and practical approximation of organ doses for comparisons between CT scanners and protocols. For example, given a hypothetical organ dose of 10 mGy and CTDI vol of 15 mGy for the protocol that delivered this dose, the percentage CTDI vol would be 10 / 15 = 0.67%.…”
Section: Ct Protocolsmentioning
confidence: 99%
“…The latter approach, first proposed by Huda et al [21], provides an accurate and practical approximation of organ doses for comparisons between CT scanners and protocols. For example, given a hypothetical organ dose of 10 mGy and CTDI vol of 15 mGy for the protocol that delivered this dose, the percentage CTDI vol would be 10 / 15 = 0.67%.…”
Section: Ct Protocolsmentioning
confidence: 99%
“…11,12 As a result, the reported CTDI vol -to-organ-dose conversion coefficients were valid only for that specific scan protocol and patient model. Several investigators [13][14][15][16] have demonstrated that patient size has a significant effect on the absorbed dose and, even more specifically, on organ dose for a specific scanner output ͑e.g., CTDI vol ͒. These reports have all shown that for the same exposure conditions ͑i.e., same technical parameter settings͒, organs in smaller patients ͑including pediatric patients͒ receive higher radiation doses than those in larger patients.…”
Section: Introductionmentioning
confidence: 99%
“…The CT dose index volume is roughly equal to the fetal dose in this patient. 2,3 The American College of Radiology's CT accreditation reference CTDI vol in abdominal CT is 25 mGy, which corresponds to an embryo dose of B35 mGy in a 70-kg patient. Thus, our fetal dose was within acceptable limits.…”
Section: Denouement and Discussionmentioning
confidence: 99%